The concept of Rusydi Ahmad Thu'aimah in the Arabic Textbook MI Ministry of Religious Affairs / Konsep Rusydi Ahmad Thu'aimah dalam Buku Teks Bahasa Arab MI Kementerian Agama - Sugirma Sugirma; Dian Risky Amalia; Nurhadi Nurhadi; Wildana Wargadinata; Siti Sulaikho (Universitas Islam DDI AGH Abdurrahman Ambo Dalle Polewali Mandar, Sulawesi Barat, 2024)
The Arabic textbook of MI Ministry of Religious Affairs became a national textbook and became a guide for other supporting books such as LKS at the Madrasah level. The quality and effectiveness of the book